Determinants of action to obtain the covid-19 vaccine in the Moi indigenous community - Hansen Maikel Su; Jenni Lilis S Siagian; Yosef Madai (Journal of Midwifery and Nursing, 2025)
The covid-19 virus is one of the most dangerous diseases today, due to the high number of cases and deaths. Efforts that can be made for prevention are vaccines. However, only 42.54% of all vaccine targets in West Papua Province have received the complete vaccine. The community argues that this vaccine is not in accordance with customs, religion, accelerates death. the purpose of this study was to determine the determinants of action to get the covid-19 vaccine in the Moi indigenous people. This study was conducted with a cross sectional approach, which was conducted at the Aimas Convention Centre Hotel, Sorong Regency. The study population was all participants in the Moi Tribe's traditional trial activities in Greater Sorong and a sample of 234 people. Data were collected using a questionnaire and analysed using the Spearman Rank test. The test results showed that knowledge p-value 0.000 (there is an influence), vaccine ability confidence 0.687 (no influence), socialisation impact 0.017 (there is an influence) and perception 0.355 (no influence). It is hoped that the indigenous community management board will collaborate with the local health office in an effort to provide counselling on the importance of the covid-19 vaccine